Reassembling Curricular Concepts: a Multimodal Approach to the Study of Curriculum and Instruction - Tang, Kok-Sing (Springer Netherlands, 2011)
Based on the multidisciplinary field of multimodality, this paper offers a theoretical perspective on the construct of a curricular concept which is commonly used in a school curriculum and applies it to an analysis of a typical curricular text and classroom instruction that exposit the physics concept of work–energy. Theorizing a concept as a network of meaning relationships across multiple modes of representation situated in human activity, this approach examines how we can recognize the meaning constructed through the semantic relationships of language and its contextualization with pictorial, graphical, and numerical resources. The value of this approach to curriculum and instruction in formal educational settings is also presented.